Health information on social media helps mitigate Crohn's disease symptoms and improves patients' clinical course. (February 2021) - Zhao, Junzhang; Han, Hongxing; Zhong, Bu; Xie, Wenjing; Chen, Ying; Zhi, Min
Abstract: As the general public rely more on social media for accessing health information, it is important to investigate how patients with complex chronic diseases use social media for symptom management. Guided by social cognitive theory, this study analyzes Crohn's disease patients' use of health information and its impact on their clinical course. The results show that health information on social media had provided the patients significant informational, emotional, and peer support, which mediated their treatment understanding, symptom management, and trust in doctors. When their symptoms went worse, the patients reported obtaining more support from social media groups, leading to better treatment understanding. A better treatment understanding resulted in more trust in doctors. But using social media groups that were not monitored by physicians reduced their trust in doctors. Initial evidence shows that health information could benefit patients like a complementary medical intervention. As an exploratory study, the results should be interpreted with caution as some findings may not be generalized to all complex chronic disease patients. This endorses the importance of studying patients' health information processing on social media as part of the effort for improving chronic illness care. Highlights: Social media have potential to improve Crohn's disease patients' clinical course. Health information on social media offers informational, emotional and peer support. The support alters treatment understanding, symptom control, and trust in doctors. Patients' interaction with doctors on social media affects health outcomes. Health information may function like medical interventions in the clinical course.